2016
DOI: 10.1097/md.0000000000005494
|View full text |Cite|
|
Sign up to set email alerts
|

Severity of pulmonary emphysema and lung cancer

Abstract: The aim of this study was to determine the relationship between lobar severity of emphysema and lung cancer using automated lobe segmentation and emphysema quantification methods.This study included 78 patients (74 males and 4 females; mean age of 72 years) with the following conditions: pathologically proven lung cancer, available chest computed tomographic (CT) scans for lobe segmentation, and quantitative scoring of emphysema. The relationship between emphysema and lung cancer was analyzed using quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…In our study, patients with LC had emphysema located predominantly in the upper lobes, obtaining results similar to those in the literature. 37 Hohberger et al 29 found that, when comparing the location of a malignant nodule with other pulmonary regions of the same patient, the probability of having a more severe emphysema in the area where LC was present was significantly higher. In our series, we did not find that the tumor was in the lobe with more emphysema within each patient.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients with LC had emphysema located predominantly in the upper lobes, obtaining results similar to those in the literature. 37 Hohberger et al 29 found that, when comparing the location of a malignant nodule with other pulmonary regions of the same patient, the probability of having a more severe emphysema in the area where LC was present was significantly higher. In our series, we did not find that the tumor was in the lobe with more emphysema within each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Next, both lungs were differentiated from the surrounding chest wall and mediastinal structures. Lobe segmentation was then performed to allow automated delineation for each of the 5 pulmonary lobes using automatic lobe segmentation algorithm [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…A few studies have shown that regional emphysema was associated with the location of lung cancer [ 9 ]. According to Bae et al [ 12 ], more severe emphysema was found in the upper lobes and a higher frequency of lung cancer was also found in the upper lobes. In the current study, the mean RES was highest at 0.55 in the upper lobe, followed by 0.35 in the lower lobe.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, panlobular emphysema produces uniform destruction of the secondary lobule, which results in homogenous low attenuation that may involve the entire lung. Recently, several studies have reported that the severity of emphysema on CT was associated with the presence of lung cancer [ 12 , 13 ]. In the degree of COPD severity, visual emphysema, as well as the airway obstruction of lung function, were independent predictors of lung cancer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%